NUMERICAL ANALYSIS OF THE AIR-FUEL MIXTURE IN INDIRECT AND DIRECT INJECTION OF FOUR-STROKE ENGINES - Narcizo, G. G.; Miranda, D. A. (Revista de Engenharia Térmica, 2019)
The quality of the air-fuel mixture in internal combustion engines directly affects the combustion efficiency, therefore a good design of the combustion chamber combined with the correct fuel injection system, can provide a better use of this mixture and increase the efficiency of the engine. Considering these aspects, this scholarly work presents a comparative study of the indirect injection system and direct fuel injection, analyzing the way the mixture behaves in these two conditions. For this, the Ansys Fluent simulation software was used, in which were applied computational fluid dynamics simulations of the air-fuel mixture. The objective of this scholarly work is to contribute to the development of the injection systems, enabling the improvement of new studies and developments of new nozzle models can be performed.